Método dos elementos de contorno aplicado a propagação de ondas gravitacionais não lineares - Zambrozuski, Newton Jorge Munareto (1992)
This work presents a boundary element method formulation in two-dimensions, to be applied either to moving boundary problems, or to problems with non moving boundaries. Isoparametric quadratic elements have been implemented to discretize the boudary. The procedure developed for non moving boundary problems can be applied to study the hidraulic flow in rivers, reservoir and channels (open or not open). The procedure developed for moving boundary problems can be applied to simulate non-linear gravitational waves, wave makers and sloshing. A Lagrangean formulation is employed to update the boudary fluid particles at each time step. An Eulerian formulation is employed to solve the boundary value problem at each time step. Velocity potencial and normal velocities at boundary nodes, at each time are obtained by the boundary element method. The time marching process is carried out through the fourth order Runge-Kutta method. A summarized discussion concerning the numerical results of the most important problems studied is presented, including comparisons with analytical solutions whenever possible.